Primary Congenital Lymphedema Complicated by Hydrops Fetalis: A Case Report and Review of the Literature - Paul Singh; Matthew Connell (Case Reports in Obstetrics and Gynecology)
Introduction. Primary congenital lymphedema is a rare disorder associated with insufficient development of lymphatic vessels. Usually most patients present with lower extremity edema seen sonographically. Rarely primary congenital lymphedema may be associated with severe lymphatic dysfunction resulting in hydrops fetalis. Case. A 27-year-old primigravida with a family history of leg swelling throughout multiple generations was diagnosed early in the third trimester with hydrops fetalis. Delivery was undertaken at 32 weeks for nonreassuring fetal status and the infant expired at approximately 45 minutes of life. Primary congenital lymphedema was confirmed via molecular testing of the vascular endothelial growth factor receptor-3 gene. Discussion. The diagnosis of PCL is suspected prenatally when ultrasound findings coincide with a positive family history of chronic lower limb lymphedema. Isolated PCL is rarely associated with significant complications. Rarely, however, widespread lymphatic dysplasia may occur, possibly resulting in nonimmune hydrops fetalis.